PENGARUH PROFITABILITAS, UMUR, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Jefrianus Mau; Indri Prasasyaningsih; Putriana Kristanti (Jurnal Riset Akuntansi dan Keuangan, 2015)
; "> This study aims to examine the influence of profitability, age, and size of the company on the capitalstructure. Population in this research is the company's property and real estate listed on theIndonesia Stock Exchange in 2010-2014. There are 24 companies with the data for 5 years as manyas 120 data that meet the criteria of the study sample that has been set. Variables used in this studywere independent variables consisting of profitability as measured by ROE, firm size, firm age andthe dependent variable is capital structure. These results indicate that profitability as measured byROE negative effect on the capital structure, age did not affect the company's capital structure andthe size of the company's positive impact on the capital structure.Keywords: profitability, firm’s age, firm’s size, capital structure